Developing an IoT and ML-driven platform for fruit ripeness evaluation and spoilage detection: A case study on bananas - Rajini M; Persis Voola (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Food waste is a significant global problem that demands immediate action to reduce it. This study presents a novel framework that merges Internet of Things (IoT) and machine learning (ML) technologies to detect fruit ripeness and spoilage, which is essential in minimizing losses in the cold chain process of fresh produce industry. The study employed temperature, humidity, and gas emission sensors along with an ESP32 microcontroller to establish a unique framework that achieved exceptional accuracy in predicting banana ripeness stages. This framework employed various machine learning algorithms to detect ripeness stages, with the CatBoost classifier exhibiting exceptional performance, demonstrating its dependability and effectiveness in assessing fruit quality. The benefits of this research extend beyond fruit ripeness detection and pave the way for future advancements in automating quality assessment in agricultural supply chains.